Patient perceptions of successful hepatitis C virus treatment adherence in Veterans. Issue 5 (24th August 2021) - Zhang, Grace Y.; Patel, Krupa; Agbalajobi, Olufunso; Alexandre, Wheytnie; Reid, Andrea; Serper, Marina; Calgaro, Linda; Zickmund, Susan; Coppler, Tami; Mizah, Margaret; Shaikh, Obaid; Rogal, Shari
Abstract: Background: Treatment adherence remains a potential barrier to achieving population‐level hepatitis C virus (HCV) elimination by 2030. We aimed to understand barriers to and facilitators of HCV treatment adherence pre‐ and post‐direct‐acting antiviral (DAA) treatment. Methods: A cohort of US Veterans who were initiating DAA treatment completed pre‐ and post‐treatment surveys assessing demographic information, psychological symptoms and perceived barriers to adherence. DAA adherence was assessed through self‐report and pharmacy records. Sustained virologic response (SVR) was evaluated using the medical record. Mann‐Whitney U, Fisher's exact tests, and logistic regression were employed to evaluate associations of patient characteristics and survey responses with adherence and SVR. Results: Of 97 participants, the majority were male (98%), white (62%), low‐income (less than 35 000/y; 82%), and had a history of self‐reported prior substance use (93%). The most common anticipated adherence barrier prior to treatment was having side effects (21%). Over follow‐up, 62% of participants missed doses and 84% achieved SVR. Decreased pain (OR 0.32, 95% CI 1.06‐1.72), agreeing with 'the medication will improve my health' (OR 4, 95% CI 1.22‐15.8) and disagreeing with being 'worried about my liver disease getting worse' (OR 0.2, 95% CI 0.05, 0.59) predicted successfully achieving SVR. After treatment, the most commonly reported barriers to adherence were being busy (13%) and being away from home (13%). Veterans reported non‐significantly decreased substance use after treatment (38% vs 28%, P = .18). Conclusion: In this population of Veterans with high rates of substance use, most participants missed doses but still achieved SVR. HCV treatment may also serve as an opportunity for substance use treatment.